Peran Manajemen Kelas Dalam Meningkatkan Efektifitas Proses Pembelajaran - Muhammad Aufa Muis; Mardiana Mardiana; Nurlidia Putri; Sucita Febriani; Isma Yuniarti (Departement of Mathematics Education, 2025)
Classroom management is one of the factors that significantly influences the quality and effectiveness of the learning process in schools. Effective classroom management can create a conducive learning environment and support students in better understanding the learning materials. The purpose of this study is to analyze the role of classroom management in improving the effectiveness of the learning process. Using a qualitative descriptive approach, this research explores various aspects of classroom management that can affect the teaching and learning atmosphere, such as classroom arrangement, time management, and interpersonal relationships between teachers and students. The results indicate that good classroom management can enhance students' attention, minimize disruptions during the learning process, and help students focus more on the material being taught. Therefore, effective classroom management plays a crucial role in improving learning effectiveness.